Validation of the Iranian version of the childbirth experience questionnaire 2.0 - Solmaz Ghanbari-Homayi; Anna Dencker; Zahra Fardiazar; Mohammad Asghari Jafarabadi; Sakineh Mohammad-Al; Shahla Meedya; Eesa Mohammadi; Mojgan Mirghafourvand (BMC, 2019)
Abstract Background Assessing women's childbirth experiences is a crucial indicator in maternity services because negative childbirth experiences are associated with maternal mortalities and morbidities. Due to the high caesarean birth rate in Iran, measuring childbirth experience is a top priority, however, there is no standard tool to measure this key indicator in Iran. The aim of present study is to adapt the "Childbirth Experience Questionnaire 2.0" to the Iranian context and determine its psychometric characteristics. Methods Childbirth Experience Questionnaire 2.0 was translated into Farsi. A total of 500 primiparous women, at 4 to 16 weeks postpartum, were randomly selected from 54 healthcare centres in Tabriz. Internal consistency and reliability was calculated using the Cronbach's Coefficient alpha and Intraclass Correlation Coefficient, respectively. Construct validity was assessed using exploratory and confirmatory factor analysis and discriminant validity using the known-group method and the Mann-Whitney U-test. Results The internal consistency and reliability for the total tool were high (Cronbach's alpha = 0.93; Intraclass Correlation Coefficient = 0.97). Explanatory factor analysis demonstrated the adequacy of the sampling (Kaiser-Meyer-Olkin = 0.923) and significant factorable sphericity (p < 0.001). Confirmation factor analysis demonstrated acceptable values of fitness (RMSEA = 0.07, SRMSEA = 0.06, TLI = 0.97, CFI > 0.91, x 2/ df = 4.23). Discriminatory validity of the tool was confirmed where the CEQ score and its subdomains were significantly higher in women who reported having control over their childbirth than women who did not. Conclusion The Farsi version of the Childbirth Experience Questionnaire 2.0 tool is a valid and reliable tool and can be used to measure the childbirth experience in Iranian women.